ESTETIKA UNSUR-UNSUR ARSITEKTUR BANGUNAN MASJID AGUNG SURAKARTA (Universitas Negeri Semarang, 2015)
Masjid merupakan produk budaya yang terkait sistem ide dan aktifitas masyarakat. Secara fisik, Bentuk Masjid Agung Surakarta didasari oleh pandangan hidup yang berakar pada kepercayaan masyarakat penghuninya, yang memiliki keyakinan agama Islam-Jawa yang berkaitan dengan Hindu-Budha. Secara khusus, penelitian ini bertujuan (1) melakukan identifikasi dan menganalisis unsur-unsur arsitektur bangunan Masjid Agung Surakarta, (2) menganalisis makna unsur-unsur arsitektur bangunan Masjid Agung Surakarta, (3) menelusuri dan menganalisis nilai-nilai kearifan lokal yang terkandung di dalam makna bentuk dan struktur unsur-unsur arsitektur bangunan Masjid Agung Surakarta. Penelitian ini menggunakan metode kualitatif dan melalui kajian semiotika dengan menggunakan teori Carles Sander Peirce dan Roland Barthes untuk menemukan arti/ pesan melalui tanda-tanda yang didapat pada unsur-unsur arsitektur bangunan Masjid Agung Surakarta. Hasil yang diperoleh menjelaskan bahwa (1) unsur-unsur arsitektur bangunan Masjid Agung Surakarta memiliki ciri-ciri visual mirip rumah tradisional Jawa yaitu Rumah Joglo, (2) penciptaan unsur-unsur arsitektur bangunan Masjid Agung Surakarta merupakan simbol yang memiliki makna, (3) dari makna unsur-unsur arsitektur bangunan Masjid Agung Surakarta terdapat pendidikan nilai-nilai kearifan lokal yang dapat diambil yaitu nilai kebenaran, nilai moral, nilai estetika dan nilai religius. The mosque is a cultural product related to the system of ideas and community activities. Physically, Great Mosque of Surakarta forms based on a view of life that is rooted in public confidence inhabitants, which has a Java-Islamic religious beliefs associated with Hindu-Buddhist. Specifically, this study aims to (1) To identify and analyze elements architecture the Great Mosque of Surakarta, (2) to analyze architecture elements Great Mosque of Surakarta, (3) Browse and analyze the local wisdom values contained in within the meaning of form and structure architectural elements. This study used qualitative methods and through the study semiotics by using theory of Carles Sander Peirce and Roland Barthes to find meaning by the signs that come on the elements architecture Great Mosque of Surakarta. The results explain that (1) the elements architecture Great Mosque of Surakarta have similar visual characteristics of a traditional Javanese house is Joglo, (2) the creation of architectural elements Great Mosque of Surakarta is a symbol that has meaning, (3) of the meaning architectural elements Great Mosque of Surakarta are educational values ​​of local wisdom that can be taken is the value of truth, moral values, aesthetic values ​​and religious values The mosque is a cultural product related to the system of ideas and community activities. Physically, Great Mosque of Surakarta forms based on a view of life that is rooted in public confidence inhabitants, which has a Java-Islamic religious beliefs associated with Hindu-Buddhist. Specifically, this study aims to (1) To identify and analyze elements architecture the Great Mosque of Surakarta, (2) to analyze architecture elements Great Mosque of Surakarta, (3) Browse and analyze the local wisdom values contained in within the meaning of form and structure architectural elements. This study used qualitative methods and through the study semiotics by using theory of Carles Sander Peirce and Roland Barthes to find meaning by the signs that come on the elements architecture Great Mosque of Surakarta. The results explain that (1) the elements architecture Great Mosque of Surakarta have similar visual characteristics of a traditional Javanese house is Joglo, (2) the creation of architectural elements Great Mosque of Surakarta is a symbol that has meaning, (3) of the meaning architectural elements Great Mosque of Surakarta are educational values ​​of local wisdom that can be taken is the value of truth, moral values, aesthetic values ​​and religious values.